Iowa Birdline update, March 27-30, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Email for the Iowa Birdline update for March 27-30, 1995. The highlights for the update include sightings of a Fulvous Whistling-Duck, Mountain Bluebird, Cinnamon Teal, Sandhill Cranes, a pair of Peregrine Falcons and an exotic Bar-headed Goose. Epson - sheet feed/flatbed